Exposición a riesgo ocupacional y conocimiento del personal de enfermería Nuevo Chimbote - Ortiz Palacios, Doris Natali (2016)
This research is quantitative descriptive correlational type, with the purpose to determine the relationship between the level of knowledge and degree of exposure to occupational hazard of nurses from the health center Nuevo Chimbote, 2015. The sampling universe was composed by 20 nurses and 13 nursing technicians who met the criteria. Data were collected through two instruments, a questionnaire to measure the level of knowledge on occupational health and an observation guide of exposure to occupational risk, these were made by the author. With the application of these instruments the following results: 1. There is a statistically significant relationship between the degree of exposure to occupational risk and the level of knowledge of nursing staff (P = 0.01). 2. 100% of registered nurses are exposed to high occupational risk; and as for the technical staff in nursing, it shows that 85% is exposed to a high occupational risk but 15% to 70% moderado.3.El occupational hazard of licensed nurses regularly show a level of knowledge, 25% a high level and only 5% with a low level; unlike the technical nurses prevailing low awareness level with 69% and 31% with a regular level.